Modernizing the Mobility Air Force for Tomorrow's Air Traffic Management System - Bednarz, Sean (RAND Corporation, 2012)
Aircraft modernization to comply with mandates affecting airspace ensures continued access to fuel-efficient cruising altitudes and use of the busiest airports, but these future benefits require an upfront investment in avionics upgrade programs. Building on RAND work examining the cost-effectiveness of modernizing the U.S. Air Force's KC-10 aerial refueling tanker, this study extended the analysis to the C-5, C-17, C-130, and KC-135 fleets.